Improving The Performance Of Solar Concentrator Systems With The Method Of Light Refraction And Reduction Of The Effects Of Sunlight Radiation - Syah, Muhammad Aslam (Al-Makki Publisher, 2025)
Solar panels are the conversion of sunlight into electricity, either directly using photovoltaics, or indirectly using concentrated solar power to produce electricity for homes and buildings that use electricity sources. Solar panels As a more efficient and more affordable solar power system to take advantage of economic and environmental benefits. Solar panels are not only used in homes, solar panels are used in remote areas and areas of schools that lack electricity, communities and telecommunications equipment and water pumps. The use of renewable resources has been greatly encouraged since the turn of the century due to the limited sources of fossil fuels. The richest fuel source in the field of renewable energy is solar energy. This experimental-development study focuses on the manufacture and testing of an off-grid solar charging system with the utilization of light by increasing the level of its intensity capture. It also focuses on determining the effectiveness of the solar concentrator system on voltage and current as well as output power and also one of the factors that can affect the efficiency of solar panels is the temperature of the solar panel module. The efficiency of solar panels will decrease as the temperature of the solar panels increases. Therefore, a cooling mechanism is needed in the form of a transparent water container to absorb solar heat and transmit its light without heat radiation on the surface of the solar panel to be able to increase the efficiency of the solar panel.